Comparative Study of the Structure and Properties of Poly(Vinylidene Fluoride)/Montmorillonite-Polypyrrole Nanocomposites Prepared by Electrospinning and Solution Casting - Schiefferdecker, Vinicius de M.; Barra, Guilherme M. O.; Ramôa, Silvia D. A. S.; Merlini, Claudia (Frontiers in Materials, 2019)
In this work, non-woven mats of poly(vinylidene fluoride) (PVDF) containing different weight fractions (2.5, 5, 10 and 12.5 wt%) of a nanostructured conductive additive based on montmorillonite - dodecylbenzenesulfonic acid - doped polypyrrole (Mt-PPy.DBSA) have been prepared by electrospinning. The effect of Mt-PPy.DBSA content on the properties of PVDF solution, mats morphology, thermo-mechanical and electrical properties was investigated. Polymorphism of PVDF/Mt-PPy.DBSA mats was investigated by Fourier Transform Infrared (FTIR) spectroscopy. Moreover, the electromagnetic interference shielding effectiveness (EMI SE) and EMI attenuation mechanism was investigated. In order to perform a comparative study, nanocomposites with the same weight fraction of Mt-PPy.DBSA was also prepared by solution casting. The PVDF/Mt-PPy.DBSA mats display fibers with smaller diameters than neat PVDF, due to the increment in the ionic conductivity of the solution. The incorporation of the Mt-PPy.DBSA additive slightly improved electrical conductivity of the mats and they behave like as an electrically insulating material (10-14 S cm-1), due to their porosity, that prevents the formation of a conducting network. Furthermore, the EMI SE of electrospun mats is practically null, indicating that they are almost transparent to magnetic waves. On the other hand, nanocomposites fabricated by solution casting display superior electrical conductivity (10-2 S cm-1) and EMI SE reached values of -5 dB.